Reliability Improvement of Multilevel Hybrid Active Neutral-Point-Clamped Inverters - HAKAMI SAMER SALEH EBRAHIM (The Graduate School, Ajou University, 2024)
This dissertation focuses on improving the reliability of multilevel hybrid active neutral- point-clamped (ANPC) inverters through a series of proposed works. The primary objective is to address key challenges and enhance the overall performance and reliability of multilevel hybrid ANPC inverters. Among multilevel hybrid ANPC inverters, three- and five-level are considered due to their wide utilization in both academia and industries. The first research work aims to enhance the operation of five-level hybrid ANPC inverter in the high-frequency switching region. A mathematical model is developed to select the most appropriate flying capacitors (FCs) for the five-level hybrid ANPC inverter, eliminating the need for complex pre-charging algorithms or external hardware. This model ensures the desired output voltage level (i.e., five-level pole voltage), further enhancing the performance of the inverters with reduced distortion on the output voltages. The second research work introduces a dual-reference voltage-based pulse width modulation (DRV-PWM) scheme for three-phase five-level hybrid ANPC inverters. This scheme, as an alternative switching scheme, provides the benefits of conventional phase- shifted-carrier-based PWM (PSC-PWM) by naturally balancing voltages without the need for voltage sensors. Additionally, it effectively balances thermal losses across the three phases, thereby improving the reliability and efficiency of the switching devices in the five- level hybrid ANPC inverter. The final research work proposes creative modulation schemes based on modified carrier-based PWM with an offset injection to extend the modulation index (MI) to a maximum of 115% (i.e., modified space vector PWM (SVPWM)). By applying these schemes, the lifetime of dc-link capacitors in three-level and five-level hybrid ANPC inverters is enhanced, resulting in improved reliability of the inverters thought the reduction of ripples in both the neutral-point current and common mode voltage (CMV). The research methodology involves a comprehensive analysis of the proposed works with detailed description of system modelling, conventional methods and related studies and addressing their limitations. In addition, the proposed methods are extensively explained to clarify the contribution in improving the overall performance and enhancing inverters reliability. Simulation studies and theoretical analyses are conducted to evaluate the performance and effectiveness of the proposed schemes. The outcomes demonstrate significant improvements in the reliability and efficiency of hybrid ANPC inverters. Overall, this research contributes to advancing the field of multilevel (three- and five- level) hybrid ANPC inverter technology by addressing crucial challenges and proposing innovative solutions to enhance their reliability especially the capacitors and switching devices. The developed modulation schemes and strategies offer valuable insights and practical applications for the design and implementation of reliable hybrid ANPC inverters in various power electronic systems.
학위논문(박사)--전자공학과,2024. 2
Keywords: DC-link Ripple Suppression; Multilevel ANPC Inverters; PWM; Reliability